THE EFFECT OF BRAND EXPERIENCE, BRAND IDENTIFICATION, BRAND AUTHENTICITY, AND BRAND LOVE ON BRAND LOYALTY IN WAROENG KALIGARONG RESTAURANT IN SEMARANG CITY - Anita Meilawati; Augusty Tae Ferdinand (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The development of the restaurant industry sector in Indonesia is growing. The development of the restaurant industry sector is one of the sectors driving economic growth that can increase national income. This can be seen from the consistency of the number of new restaurant and hotel openings throughout Indonesia. In addition, the restaurant industry sector in Indonesia is a popular and promising culinary business. The purpose of this study was to determine the effect of brand experience, brand identification, brand authenticity, brand love and brand loyalty. Analysis using SEM showed several findings:Brand Experienceon Brand Identification shows that there is a significant and positive effect, Brand Identification on Brand Love shows that there is a significant and positive influence, Brand Authenticity on Brand Love shows that there is a significant and positive influence, Brand Identification on Brand Loyalty shows that there is a significant and positive influence and Brand Love on Brand Loyalty shows that there is a significant and positive influence Keyword : Brand Experience, Brand Identification, Brand Authenticity, Brand Love, Brand Loyalty, SEM